Implementation of the Baznas Management Information System at the National Board of Zakat in Bekasi City - Rafi, Muhammad Sulthan (Indo Consultan Energi, 2024)
The BAZNAS Management Information System (SIMBA) is a breakthrough for the National Zakat Amil Agency (BAZNAS) in optimizing the achievement of zakat management objectives. This research aims to describe the implementation of SIMBA at BAZNAS Bekasi City. This research also aims to identify supporting and inhibiting factors for SIMBA at BAZNAS Bekasi City. This research uses a qualitative method with a descriptive approach. The validity technique uses a triangulation approach. The data source comes from informants at BAZNAS Bekasi City. This research shows that the implementation of SIMBA at BAZNAS Bekasi City consists of three phases: input, process, and output. Supporting factors in implementing SIMBA at BAZNAS Bekasi City are competent human resources, supporting facilities and training. Meanwhile, the inhibiting factor in implementing SIMBA at BAZNAS Bekasi City is the delay in sending data by the Zakat Collection Unit (UPZ) to BAZNAS Bekasi City. Therefore, BAZNAS must pay attention to UPZ so data can be transmitted on time.